Ecotoxicity of rare earths in the marine mussel Mytilus galloprovincialis and a preliminary approach to assess environmental risk - Mestre, Nélia (2020)
The increasing use of rare earth elements (REEs) in diverse technological applications has augmented the demand and exploitation of these worldwide, leading to a higher input of REEs + Yttrium (Y) in the marine environment. The present study investigated the ecotoxicity of Lanthanum (La) and Y to Mytilus galloprovincialis developing embryos and juveniles. This was achieved by quantifying the embryogenesis success after 48 h, and survival of juveniles after 96 h of exposure to different concentrations of La and Y. Results show that both La and Y are more toxic to developing embryos and larvae than to juveniles of M. galloprovincialis. Predicted no-effect concentration (PNEC) values were also derived for the embryo development as a preliminary approach to assess the environmental risk for these compounds to marine organisms. Results revealed that La is more toxic than Y. The high sensitivity of the early developmental stages to these compounds highlight the relevance of including these stages when evaluating the toxicity of chemicals where little information is available. Although older life stages may be more tolerant to toxicants, the population survival will be compromised if new recruits are not viable, with implications to the whole ecosystem health and functioning of the impacted area. Information on the ecotoxicity of chemicals with expanded technological use and that may be released during deep-sea mining activities is urgent in order to help estimate environmental impacts.